Evaluating the social support and self-esteem towards work-family enrichment in achieving life satisfaction - Wan Rashid, Wan Edura; Nordin, Mohamad Sahari; Omar, Azura; Ismail, Izhairi (2011)
Most of the past researchers have focused on the negative consequences in managing work and family roles. Yet, little attention has been given to the potential psychological outcomes of participating in multiple roles such as enrichment. Thus, this study was to validate the hypothesized interrelationships among the predictors of work-family enrichment and life satisfaction among nurses of public hospitals in Malaysia. In addition, it was also examined the likely mediation effect of work-family enrichment on support and selfesteem- life satisfaction relationship. Data relating to the constructs were collected from 689 female married nurses from public hospitals in Malaysia and were subjected to a structural equation modeling analysis using AMOS 18 data-fitting program. The results established statistically substantial and significant path coefficients. Finally, the implications and recommendations of these finding were discussed.